Towards population-based genetic screenings for breast and ovarian cancer: A comprehensive review from economic evaluations to patient perspectives. (August 2021) - Ficarazzi, Filomena; Vecchi, Manuela; Ferrari, Maurizio; Pierotti, Marco A.
Abstract: Genetic testing for hereditary breast and ovarian cancer following genetic counseling is based on guidelines that take into account particular features of the personal and family history, and clinical criteria conferring a probability of having a BRCA mutation greater than 10% as a threshold for accessing the test. However, besides reducing mortality and social impact, the extension of screening programs also for healthy family members would allow a huge saving of the rising costs associated with these pathologies, supporting the choice of the "Test" strategy versus a "No Test" one. Analyses of different health care systems show that by applying the "Test" strategy on patients and their families, a decrease in breast and ovarian cancer cases is achieved, as well as a substantial decrease in costs of economic resources, including the costs of the clinical management of early detected tumors. In this review, we analyzed the most recent papers published on this topic and we summarized the findings on the economic evaluations related to breast and ovarian cancer population screenings. These results proved and validated that the population-wide testing approach is a more accurate screening and preventive intervention than traditional guidelines based on personal/family history and clinical criteria to reduce breast and ovarian cancer risk. Highlights: BRCA Population Screening programs, would allow a decrease in cancer cases and also savings in economic resources. The use of guidelines alone can lead to a loss of individuals (30% of patients and 10% of unaffected) with BRCA mutations. Current international guidelines for BRCA genetic testing, require further optimization and harmonization across countries. The population-based BRCA screening approach is cost-saving and highly cost-effective compared to guidelines approach.